RANCANG BANGUN SISTEM RESERVASI PARKIR ONLINE PADA PUSAT PERBELANJAAN DI KOTA DENPASAR BERBASIS WEB - Iga Wilhamdika, Gede; Arsa Suyadnya, I Made; Oka Saputra, Komang (Jurnal SPEKTRUM, 2019)
Shopping centers today are a shopping and recreation destination for the community. The problem that is often faced by managers of shopping centers is parking. The rapid development of information technology today can be used to build an application that is used to facilitate the driver in getting a parking space. In this study, a parking reservation application was developed which can be used to make it easier for visitors to the shopping center to get a parking space. Application development starts from the stage of system needs analysis, system modeling, system making up to system testing. This application is built using the PHP programming language and MySQL database. The results of this study are the application of responsive web-based online parking reservation system, where responsive web can adapt to the large or small smartphone screens used. This application is also integrated with geographic information services that are useful for displaying available parking locations. This application can ensure that shopping mall visitors get a parking slot after making a reservation. Tests carried out on this application with the Black-Box method, the functional application has been running well and based on the System Usability Scale test, the average value obtained from twenty respondents is 81.13 which is in the Acceptable category or can be accepted by the user.